GENE-48. ANALYSIS OF HUMAN BRAIN TISSUE TRANSCRIPTOME TO IDENTIFY RISK GENES AND ALTERED MOLECULAR PATHWAYS IN GLIOMA-RELATED SEIZURES. (11th November 2019) - Feyissa, Anteneh; Carrano, Anna; Wang, Xue; Allen, Mariet; Ertekin-Taner, Nilufer; Rosenfeld, Steven; Guerrero-Cazares, Hugo; Quinones-Hinojosa, Alfredo
Abstract: OBJECTIVE: Our goal is to identify new pathways perturbed in and which may lead to GRS. METHODS: We collected brain transcriptome levels from healthy controls (n=5), patients with GRS (n=9), glioma without seizures (non-GRS, n=8), and idiopathic temporal lobe epilepsy (iTLE, n=7) using Illumina-based poly-A capture high-throughput RNA sequencing approach. Differential gene expression analysis was conducted to ascertain expression differences between the four groups. We identified molecular pathways enriched for differentially expressed genes (DEG) using Ingenuity Pathway Analysis. DEGs were defined as those with log2 fold change ≥ 2 and q-value < 0.01 when compared to GRS. RESULTS: Principal component analysis revealed that diagnostic grouping was the main determinant of the transcriptome variance. We identified 212 DEGs in the GRS vs. non-GRS analysis. Among these, 108 genes were up-regulated and 104 genes were down-regulated. Among the genes that were down‐regulated, there was significant enrichment for those involved in acute phase response signaling and immune cell trafficking (e.g. H19, BMP5, CXCL8). Compared to iTLE samples, there were 1015 DEGs in the GRS samples. Among these 877 genes were up-regulated and 138 genes were down-regulated. There was significant enrichment for genes involved in cell-to-cell signaling among those that were either uniquely up‐regulated (e.g. NRK, RGS10, SLC4A4, and SELPLG) or down‐regulated in the GRS samples (e.g. SLC9A3 –Na+/H+ exchanger; SLC5A5-sodium-glucose co-transporter family). Further, two of the most down-regulated genes in samples with GRS, SCLC17A6- vesicular glutamate transporter 2 and FOSB, have previously been shown to be involved in glutamatergic transmission. CONCLUSIONS: Our findings suggest that inflammation-related processes and alterations in cell-to cell signaling may underlie the pathogenesis of GRS. Our results also provide support for perturbations in glutamatergic transmission in GRS. Our findings require replication in larger human cohorts and functional experiments to explore the function of the genes perturbed in GRS.